A curriculum for professional preparation in health education for the University of the Philippines - Ramos, Paz Gomez 1923- (1959)
The purpose of the study is to develop a curriculum plan for professional preparation in health education for the University of the Philippines. The curricular experiences incorporated in this plan are designed to prepare prospective health education teachers in the Philippine secondary schools for three major functions: (1) responsibility for the school health education program; (2) coordination within the school, and between the school and the community; and (3) health leadership in the community.